Resíduo do abacaxi e da manga na restrição alimentar qualitativa em dietas de suínos em terminação. - Oliveira, Aparecida da Costa (2015)
Two experiments were conducted to evaluate the pineapple and mango waste on qualitative food restriction in swine termination diets. In the biological and metabolic evaluation experiment, eighteen castrated Agroceres lineage male pigs were used, with average weight of 70.00 ± 2.6 kg. The pineapple and mango bran waste had 734.39 and 1284.17 kcal of digestible energy, 509.16 and 1119.43 kcal of metabolizable energy, 2.61 and 5.53% of digestible protein and 40.80, 24.22% of digestible neutral fiber detergent and 6.63 and 9.01 of digestible acid fiber detergent, respectively. Indicating its potential to be used in qualitative feed restriction programs. In the second experiment were used thirty castrated male pigs, from the Dalland commercial line, with average initial and final weight of 74.48 ± 2.81 and 135.70 ± 7.20kg getting restrictive levels diets like 0, 10 and 20% of dietary energy with pineapple and mango bran waste utilization, being evaluated for performance, digestibility and diets economic viability. After slaughter (135.72 ± 7.20 kg) were evaluated the carcass quantitative characteristics, the digestive organs weight, the small intestine histological analysis and meat quality. Animals fed with the brans had adaptive responses, such as increased the organs weights of the digestive system and changed the villi height, mucosal thickness and vilo: crypt relation. As for the other variables analyzed the pineapple and mango bran processing waste can be used at levels of up to 10% of energy restriction, provided that, subject to the ingredients and local economic viability.